Death by chocolate frosted doughnut - Graves, Sarah, 1951- (New York, NY : Kensington Publishing Corporation, 2020)
Everything is shipshape at Jake and Ellie's new waterfront bakery, The Chocolate Moose, especially now that the annual Pirate Festival is dropping anchor in their quaint island village of Eastport, Maine. Jake and Ellie are ready for the bounty of tourists sure to flood their shop. But their plans quickly sink when the body of celebrity foodie, Henry Hadlyme, is discovered in the Moose's basement. Jake and Ellie are horrified, but their shock turns to dismay when Jake is pegged for the murder.
Includes a recipe.
Maine author.
Keywords: Tiptree, Jacobia (Fictitious character) -- Fiction; Women detectives -- Fiction; Bakers -- Fiction; Food writers -- Fiction; Friendship -- Fiction; Festivals -- Fiction; Murder -- Investigation -- Fiction; Eastport (Me.) -- Fiction; Maine -- Fiction; Detective and mystery fiction